Significance of the cranial venous system in anthropogenesis in the light of contemporary clinical and experimental data - Wysocki, Jarosław (Polskie Towarzystwo Antropologiczne, 1997)
The manner of the appearance of the Hominidae family is still a very controversial issue, since there is no general agreement among the authors upon whether it was an isolated and extraordinary event in the natural history or rather a necessary consequence of the evolution process. Rapid augmentation of the cranium capacity which occurred in this group had been probably preceded by the development of the erect body posture. Elevation of the head created new, better conditions for the outflow of the venous blood from the cranium due to the involvement of the gravitation force into this mechanism. A new model of venous outflow from the cranium must have been developed.